A biomimetic remora disc with tunable, reversible adhesion for surface sliding and skimming. (1st May 2022) - Wang, Siqi; Li, Lei; Zhao, Wei; Zhang, Yiyuan; Wen, Li
Abstract: Remora suckerfish ( Echeneis naucrates ) can perform skimming and sliding motions on the surfaces of moving hosts to optimize adhesion positions. We found that remora achieve skimming and sliding motions through coordinated movement of the suction disc's lamellae and lip locomotion through live animal observations. We implemented an integrated biomimetic remora suction disc based on morphological and kinematic data of biological remoras. With soft actuators enabling 'compression–rotation' and 'compression–extension', the biomimetic disc controls the disc lip and lamellar movement under driving with only one degree of freedom, and can switch freely between three states: zero, low-friction, and robust adhesion. Then we investigate the effects of the biomimetic suction-disc soft-lip material, preload, and lamellar movement on the tangential friction force (both forward and backward) under different adhesion states. This biomimetic suction disc with a low-modulus soft lip can adhere to a smooth surface under 0.1 N preload and achieve normal adhesion-force and tangential frictional-force control ranges spanning ∼10 −1 to ∼10 2 N and ∼10 −1 to ∼10 1 N, respectively. The results reveal how remora disc achieved fast, tunable adhesion for skimming and sliding on surfaces. Furthermore, we demonstrate a bio-inspired robot capable of attachment, detachment, skimming, and sliding motions with the aiding of simple biomimetic pectoral-fin flapping. This study lays a foundation for future integrated applications of underwater adhesion robots and related biomechanical exploration.